Kajian Drug Related Problems (DRPs) Terhadap Pengobatan Pasien Stroke Iskemik di Rumah Sakit Pusat Otak Nasional Jakarta Periode Januari – Desember 2015 S - Meila, Okpri; Rochana, Handika Indri (Universitas Muhammadiyah Surakarta, 2017)
This study aims to determine the percentage of DRPs of ptients with ischemic stroke at Brain Center National Hospital Jakarta. Based on data from the WHO 2006, each year there are approximately 13 million new stroke patients of which approximatelly 4,4 million of them die within 12 months.When patients undergo a treatment, most patients achieve optimal results that heal diseases suffered by patients but not least the failure in therapy. Therefore, the contribution required to identify, resolve and prevent problems in drug therapy known as Drug Related Problems (DRPs). The method used in this study is cross sectional. Total sample data obtained as many as 360 samples. The results showed indications without drugs of 55.62%, drugs without indication of 15.17%, drug interactions of 10.11%, patients fail to receive the drug of 7.86%, side effects of 6.18% and less drug selection right of 5.06%. Data show that the highest percentage of DRPs are indications without drugs.